Armenia: Cross-Border Higher Education - Gharibyan, Tatevik (International Higher Education, 2017)
After independence in 1991, the higher education sector in Armenia started to reshape autonomously. Many private and transnational educational institutions started to appear on the Armenian educational market and cross-border education gained a tangible popularity. This article surveys existing cross-border educational institutions in the country and their impact on the educational landscape.